1996
DOI: 10.1177/014556139607501008
|View full text |Cite
|
Sign up to set email alerts
|

Hearing and Sjögren's Syndrome

Abstract: Immune sensorineural hearing loss is manifested in several systemic immune diseases.1,2 Although hearing loss has been previously documented in patients with Sjögren's syndrome (SS),3 the effect of SS on hearing is unclear. This prospective study was designed to assess the presence of hearing loss in 14 patients with SS and, if sensorineural hearing loss was present, to determine if the hearing loss was immune-mediated. Patients were evaluated with basic audiologic tests as well as for cellular immune inner ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
3
1
2
Order By: Relevance
“…The 78 % prevalence of hearing loss in pSS noted in our study with predominantly female population, therefore, does not reflect the commonly prevalent scenario of hearing impairment in the normal Indian population. A handful of other studies on hearing loss in pSS also report figures much higher than the Indian control population data; our figure of hearing loss in 78 % of pSS patients, however, is the highest as compared to the reports of 46 % by Tumiati et al [10], 21.4 % by Trott et al [15], 36.3 % by Hatzopoulos et al [16] and 22.5 % by Ziavara et al [17]. SNHL was the commonest hearing loss in our study (97 %) and this is similar to other studies reviewed from published literature [10,16,17].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The 78 % prevalence of hearing loss in pSS noted in our study with predominantly female population, therefore, does not reflect the commonly prevalent scenario of hearing impairment in the normal Indian population. A handful of other studies on hearing loss in pSS also report figures much higher than the Indian control population data; our figure of hearing loss in 78 % of pSS patients, however, is the highest as compared to the reports of 46 % by Tumiati et al [10], 21.4 % by Trott et al [15], 36.3 % by Hatzopoulos et al [16] and 22.5 % by Ziavara et al [17]. SNHL was the commonest hearing loss in our study (97 %) and this is similar to other studies reviewed from published literature [10,16,17].…”
Section: Discussioncontrasting
confidence: 74%
“…SNHL has been commonly reported as the first otologic manifestation of some of the autoimmune diseases [8,9,[12][13][14]. Studies have reported the prevalence of hearing loss in pSS to be in the range of 21-46 % [10,[15][16][17]. Anticardiolipin antibodies (ACA) may be associated with sudden SNHL in patients with autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The pathophysiological mechanism underlying this alteration is poorly known, but one of the most widely accepted theories proposes vascular inflammation of epineural small vessels or "vasa vasorum" as the origin of sensorineural hypoacousia. 17 In our study, we observed a higher frequency of sensorineural hearing loss in the group of patients with AS from 45 to 59 years as compared with the age-matched control population.…”
Section: Discussionmentioning
confidence: 99%
“…However, information found in current literature is scarce, and except for a few prospective studies on RA, SLE, and primary SS, remaining entities are limited to reports of isolated cases. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Ankylosing spondylitis (AS) is a chronic disorder of unknown cause and probable autoimmune etiology characterized by inflammation of the axial skeleton and a tendency to ankylosis. Its association with the presence of HLA-B27 is widely recognized, as well as the participation of immunologic reactions most likely at the level of enthesis, articular cartilage, and subchondral bone.…”
mentioning
confidence: 99%
“…της έκκρισης των δακρύων με Schirmer τεστ και ανάλυση της σύνθεσης των δακρύων (τεστ περιεκτικότητας λυσοζίμης) (1,14,87,89). Σε μελέτες αναφέρεται σε ποσοστό από 21% έως 69,8% νευροαισθητήρια βαρηκοΐα ως αποτέλεσμα προσβολής του έσω αυτιού από αυτοαντισώματα και νευροπάθειας της 8 ης εγκεφαλικής συζυγίας(94). Περίπου το ένα τέταρτο αφορά σε κοχλιακή βλάβη και απώλεια ακοής στις υψηλές συχνότητες.…”
unclassified